Analisis Pengaruh Chatbot AI terhadap Pengalaman Mahasiswa Menggunakan E-commerce - Israwati Hamsar; Nur Febrianti; Amelia Uswatun Khasanah; Annajmi Rauf; Elma Nurjannah (Academic Bright Collaboration, 2024)
As e-commerce platforms increasingly adopt AI technologies, the effectiveness of chatbot integration in enhancing user experience among students remains underexplored. This study aims to analyze the impact of AI-powered chatbots on the shopping experience of university students in Makassar. Using a quantitative approach, data were collected via structured questionnaires from 88 student respondents and analyzed through descriptive and inferential methods. The findings reveal that students perceived the chatbot as highly capable of solving complex inquiries, offering relevant solutions, and delivering efficient service. The chatbot's responsiveness and ease of use received high average scores, indicating strong user satisfaction. Furthermore, the chatbot positively influenced customer satisfaction, including increased purchase intention and likelihood to recommend. These results suggest that AI chatbots significantly contribute to enhancing service quality in e-commerce and should be strategically utilized to meet the expectations of young digital consumers.